Design and experimental research of a magnetorheological elastomer isolator working in squeeze/elongation–shear mode. (April 2018) - Tao, Yu; Rui, Xiaoting; Yang, Fufeng; Chen, Gangli; Bian, Leixiang; Zhu, Wei; Wei, Min
Due to the properties of controllable stiffness and damping, a novel isolator based on magnetorheological elastomers is introduced in this article. According to the experimental results, the initial vertical stiffness and damping coefficient of the magnetorheological elastomer isolator are 1.14 × 10 6  N/m and 495.8 N s/m, respectively. The relative increase in stiffness and damping is 66.57% and 45.55%, respectively. The isolation transmissibility and root mean square of acceleration response are reduced by 41.2% and 65.3%, respectively. To describe the magnetic-induced stress–strain relationship of the anisotropic magnetorheological elastomers, a theoretical model is presented as magnetorheological elastomers working in squeeze/elongation and shear modes simultaneously. Then, the stiffness formula relating to the magnetic field, strain, and the other demanding parameters is deduced. The analytical results of the stiffness formula are fairly in agreement with the experimental data.